Manejo del plan de emergencia para las contingencias en la empresa productos Familia Sancela del Ecuador S.A. y propuesta de diseño del plan. - SEGOVIA BALAREZO, MARIBEL ALEXANDRA (2012)
The business and industrial sectors constantly generate challenges worldwide, obliging to seek new strategies to maintain and improve their position in the market. Through the application of the last technologies, natural resources and raw material are transformed in the most optimal way to offer the best products in the global market. The identification of natural and human hazards is very important in society, for these are associated to systems: man, environment and technology. Multiple emergencies may occur at any moment, being humans the most vulnerable to endure the effects thereof. All the sectors in the country suffer the risk of imminent emergencies that may affect their environment, and somehow cause unforeseen effects and apparently non-guaranteed risks planning, contingency plans, emergency management, action plans and process intervention. This reality is an issue that causes concern among many institutions, who endeavor to take the best actions to mitigate every possible event. However, the most vulnerable sector where workers are mostly affected is the industrial sector, based on the fact that the use of technologies, both modern and obsolete, generates more risks. This added to the fact of not giving the deserved importance to the application of Emergencies Plans that mitigate the risk of possible contingencies, have produced inefficient actions by the workers. Productos Familia Sancela del Ecuador S.A., as an industrial company dedicated to manufacturing, is also vulnerable to the above mentioned situation, due to the geographical zone where it is located, added to a constant demand of adopting the last technologies, with obvious implications on the environment where the activities are developed. With the purpose of guaranteeing the wellbeing and security of all the visiting workers, contractors and interested parties, it is necessary to implement in the different production processes an Emergency Plan that allows us assess, from the beginning to the end of an event, the actions that are being taken by all the involved parties in the development of each phase.